Health Inequalities in Australians of Working Age - Nepal, B; Brown, L (Connor Court Publishing, 2011)
This book brings together a unique collection of essays on the social determinants of health from some of Australia’s leading health and social policy experts – medical professionals, academics, opinion leaders, thinkers and writers.
Determining the Future: A Fair Go and Health for All
Keywords: Disadvantage -- Inequality; Health; Health and wellbeing; Health; Disadvantage; Inequality; Health and wellbeing